The Relationship Between the Market Indices Fluctuations and Fluctuations of the Economic Situation in Poland - Widz, Ewa (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The paper examines the relationship between the stock market situation, represented by the rates of returns of the main market indices on Warsaw Stock Exchange, and the economic situation in Poland, measured by dynamics of GDP. The aim of the study is to answer the question if fluctuations of stock market indices precede GDP fluctuations. The analysis is based on the quarterly dynamics of change in the period of 2003–2014. The research shows that the correlation between dynamics of the main market indices on WSE and the GDP dynamics in Poland is positive, but moderate. Generally, the market indices fluctuations precede GDP fluctuations. However, the analysis of high rates of GDP changes proves their stronger correlation with simultaneous fluctuations of indices. In addition, it has been noticed that the analysed correlation in Poland systematically declines.